Modeling Parasite Reduction Mechanisms in Chagas Disease - Vega Royero, Shirlene Patricia (2015)
Various procedures have been proposed to reduce parasitemia during Chagas disease. Here we analyze in detail models developed to predict the possible outcomes of two of these treatments. The model solutions reproduce available experimental population data and can be used as tools to help researchers to find a cure or, at least, an optimal treatment to reduce cardiac cell damage. In particular, we study how the phase diagram describing the infection outcome is modified by the application of the ganglioside GM1, finding the optimum concentration of the drug in terms of the parameters characterizing its influence on the parasite-host interaction. We also investigate the use of the non-pathogenic parasite T. rangeli to reduce T. cruzi load in a mixed infection, finding that this method is not effective against all T. cruzi strains. Furthermore, we compare phase portraits of the evolution of the disease for a single and a mixed infection, and evaluate the cell damage as a function of the time elapsed between both infections, remarking on the temporary protective effect of the reaction to T. rangeli.